Impact of HIV-ART on the restoration of Th17 and Treg cells in blood and female genital mucosa - Caruso, María Paula (Sci Rep, 2019)
The aim of this study was to evaluate the effectiveness of antiretroviral treatment (ART) on the proportion and functions of Th17 and Treg cells in peripheral blood and female genital tract (FGT) respectively. To this aim, samples from 41 HIV-neg, 33 HIV+ ART-naïve and 32 HIV+ ART+ subjects were obtained. In peripheral blood, altered Th17 and Th17/Treg proportions were normalized in HIV+ ART+, but certain abnormal Treg and activated T-cell proportions were still observed. In FGT, abnormal patterns of secretion for Th17-related cytokines were observed in cervical mononuclear cells (CMCs) from HIV+ women, even in those from HIV+ ART+, compared to the HIV-neg group. Moreover, these altered patterns of secretion were associated with diminished levels of CXCL5 and CXCL1 chemokines and with an immunoregulatory skew in the CCL17/CCL20 ratio in ectocervix samples of these women. Finally, ART did not restore proportions of Th17-precursor cells with gut-homing potential in PBMCs, and positive correlations between these cells and the levels of IL-17F and IL-21 production by CMCs may suggest that a better homing of these cells to the intestine could also imply a better restoration of these cells in the female genital tract. These results indicate that antiretroviral treatment did not restore Th17-related immune functions completely at the female mucosal level.